Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/hjh.0000000000003247
|View full text |Cite
|
Sign up to set email alerts
|

Management of intradialytic hypertension: current evidence and future perspectives

Abstract: Intradialytic hypertension (IDH), that is, a paradoxical rise in blood pressure (BP) during or immediately after a hemodialysis session, affects approximately 10-15% of the hemodialysis population. It is currently recognized as a phenomenon of major clinical significance as recent studies have shown that BP elevation extends to the whole interdialytic interval and associates with increased cardiovascular and all-cause mortality. The pathophysiology of IDH is complex involving volume and sodium overload, endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Several mechanisms that are pathophysiologically involved in the development of this phenomenon have been proposed to be implicated in the high cardiovascular risk of these individuals [4,5,19]. Among them, volume overload and intradialytic sodium gain, endothelial dysfunction, increased arterial stiffness, overactivity of renin-angiotensin-aldosterone system and sympathetic nervous system are considered significant determinants, but these have not been extensively confirmed in human studies [4,20]. Over the past years, several studies identified the presence of IDHTN as a factor strongly associated with increased risk of cardiovascular and all-cause mortality [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms that are pathophysiologically involved in the development of this phenomenon have been proposed to be implicated in the high cardiovascular risk of these individuals [4,5,19]. Among them, volume overload and intradialytic sodium gain, endothelial dysfunction, increased arterial stiffness, overactivity of renin-angiotensin-aldosterone system and sympathetic nervous system are considered significant determinants, but these have not been extensively confirmed in human studies [4,20]. Over the past years, several studies identified the presence of IDHTN as a factor strongly associated with increased risk of cardiovascular and all-cause mortality [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized crossover trial with dialysate sodium 5 mEq/L lower versus 5 mEq/L higher than serum sodium and at least three subsequent studies with individualized or low versus standard dialysate sodium concentrations showed an effect of these interventions on intradialytic hypertension and/or systolic and diastolic BP before/after hemodialysis. 11…”
Section: Fluid Overload Endothelium and Sodium Gradientmentioning
confidence: 99%
“…2 To convince reluctant patients, it is helpful to collect data in favor of fluid overload: bioimpedance; intradialytic blood volume monitoring, a flat or positive curve indicating active intradialytic refilling; and ambulatory BP monitoring, high interdialytic BP reflecting fluid excess. Antihypertensives with proven benefit 11 may not be avoidable, but fluid removal is worth a try. The interesting study by Elsayed et al 1 reminds us that it is time to act.…”
Section: Treatment Conclusionmentioning
confidence: 99%
See 1 more Smart Citation